Unification of technical solutions used in customs control as a factor in the development of economic systems - Stupak, Y.; Syzdykova, E.; Jazykbayeva, B.; Shirshova, L.; Issayeva, A.; Niyazbekova, Sh. (E3S Web of Conferences, 2023)
Support solutions and promote the sustainable development of customs, investigate and formulate measures for the management of an innovative control model. It is difficult to underestimate the positive effect of the policy pursued by the FCS, which is also implemented on the basis of the recommendations of the World Customs Organization and the provisions of the Kyoto Convention of 1999. The time for customs formalities has been significantly reduced, electronic declaration centers have been established, allowing for the registration of goods located on the territory of different customs posts. At the same time, the number of contacts of declarants with officials has been minimized due to the categorization of foreign trade participants and the improvement of the risk management system, which allows achieving maximum efficiency with minimal invested costs of the customs authority for conducting this control. However, such an active process of introducing technical means, without which it is impossible to imagine the functioning of customs authorities today, cannot remain without flaws, manifested mainly in customs document management.